Percutaneous balloon-assisted ultrasound-guided direct glue embolization of deep femoral artery pseudoaneurysm rupture - Le, Thanh Dung (Radiol Case Rep, 2020)
Deep femoral artery pseudoaneurysm is commonly caused by arterial access in endovascular procedures. Some therapeutic options have been applied for this lesion such as: surgery, ultrasound-guided compression, direct thrombin injection, covered stent, coil embolization. One of the effective therapeutic for treatment of femoral artery pseudoaneurysm but uncommon use is percutaneous direct glue injection. We hereby report a case of right deep femoral artery pseudoaneurysm after 2-week placement of the femoral tunneled hemodialysis catheter which was successfully treated by balloon-assisted percutaneous ultrasound-guided direct glue embolization.